Pulmonary consequences on patients with pectus excavatum: Update (Archives of Pediatrics of Uruguay, 2022)
Pectus excavatum (PEX) is a thoracic wall malformation due to an alteration of the costal cartilages with subsequent sinking of the sternum. Historically, it was considered a mere aesthetic or cosmetic defect, however, in recent years, new assessment methods have been developed to evaluate the repercussions of this pathology, and there is an increasing literature that demonstrates important functional consequences. We carried out an update of this pathology’s pulmonary repercussions and analyzed the most relevant articles of the recent years. Respiratory symptoms are frequent, present in more than half of the patients. A decrease in FVC, FEV1 and PEF25%-75% has been shown; as well as the presence of a restrictive and/or obstructive pattern, an increase in RV and an alteration in respiratory dynamics. The affectation of PEX on pulmonary function has been objectified, and it has been determined categorically that this pathology has important functional consequences
Keywords: Funnel chest; Thoracic wall; Respiratory function tests